Effect of Agility Drills along with Reaction Time Exercises on Agility and Reaction Speed among Collegiate Badminton Players - Deepak Charan, Sadasivam; Hari Hara Sudan, Subramaniam; Manoj Abraham, Manoharlal (INTI International University, 2023)
Background: Badminton is a game of small margin where every milli second counts. In badminton as the shuttle moves in an incredible speed the player will have a very minimal amount of time to react and execute the shot. Reaction time and Agility are the two main important components that have to be trained along with other regular exercises. Objective: To find the effectiveness of Agility drills along with Reaction time exercises on Agility and Reaction speed among collegiate badminton players. Methods: A Quasi experimental study was conducted on 18 badminton players; they were divided into 2 groups with 9 in each group based on purposive sampling technique. Group A underwent Agility drills along with Reaction time exercises and Group B underwent conventional exercises. South east Missouri agility test was used to measure the Agility and Reaction time ruler drop test was used to measure reaction time. Results: An Independent t-test was used to compare the results between two groups. Significant difference was found on both outcome measures, the South east Missouri agility test values of group A was 11.3 seconds and in group B was 12.06 seconds. Where as in Reaction time ruler drop test values on Group A was 0.17 seconds and in Group B was 0.20 seconds. The results suggest that Group A which undergone Agility drills along with Reaction time exercises shown significant improvement than Group B that underwent conventional exercises in all parameters following intervention. Conclusion: The study concludes that the Agility drills along with Reaction time exercises is more effective in improving Agility and Reaction speed than Conventional exercises in collegiate badminton players, as it improves the hand eye coordination as well as the time required to reach the shuttle becomes faster through the increased processing rate by the sense of stimuli by the central nervous system and its response in form of motor response.